Exposing Transparency In The Wadi'ah Contract - Nada Efrilia, Maulidia; Faizal, Liky; Yasir Fauzi, Mohammad; Nurnazli (State of Islamic Institute Langsa, 2023)
The Islamic Financial Institutions play a crucial role in the economy of a country, including Indonesia, but they face challenges such as bankruptcy, insecurity, and inadequate supervision. This research examines the principle of transparency in Wadi'ah savings contracts at BTM An-Nur Mandiri Jaya from the perspectives of Shariah Economic Law and Positive Law. In this study, the researcher analyzes the application of transparency principles in Wadi'ah contracts at BTM An-Nur Mandiri Jaya, focusing on Shariah Economic Law and relevant Positive Law. A qualitative field research method is employed, supported by relevant literature. The research findings indicate that BTM An-Nur Mandiri Jaya has successfully implemented transparency principles in Wadi'ah contracts, including account opening, deposits, withdrawals, and closures, based on Shariah Economic Law. However, compliance with Positive Law, particularly POJK Number 19 of 2021 Article 32 Paragraph 1 and Law Number 1 of 2013 Article 2 Letter e, remains incomplete, as evidenced by the lack of online media access to obtain information. In conclusion, BTM An-Nur Mandiri Jaya needs to enhance transparency practices in accordance with legal provisions, especially by providing online access to information.